Factors Contributing to Physical and Non-Physical Waste Generation in Construction Industry - Sasitharan Nagapan; Ismail Abdul Rahman; Ade Asmi (International Journal of Advances in Applied Sciences, 2012)
Construction industry has been developing rapidly around the world. This development increases pressure especially in developing countries to manage construction wastes generated from the industry. The construction wastes can be grouped into physical and non-physical waste and it has impact to environment, economy and social of a country. Before it can be managed well, it is crucial to understand the root causes of the generation. This paper identifies factors that contribute to the generated construction waste. Mapping technique was adopted to extract the physical and non-physical waste factors from 30 research articles around the world. It was found 81 factors exist in construction activities which are directly contributing to waste generation. These factors are grouped into seven categories: Design, Handling, Worker, Management, Site condition, Procurement and External factor. From these factors, 63 contribute to physical waste and 73 contribute to non-physical waste. The highest frequency scored in each category of physical and non-physical waste factor is identified and explained with examples. These findings give awareness to construction stakeholder about the existence of physical and non-physical waste contributory factors.